Réponses

2013-12-05T20:50:36+01:00
Bonsoir,

1) g(2) = -4 + 4 ===> g(2) = 0
    g(2-h) = -(2 - h)² + 2(2 - h)
               = -(4 - 4h + h²)  + 4 - 2h
               = -4 + 4h - h² + 4 - 2h
               = -h² + 2h

2) g'(2)=\lim_{h\to 0}\dfrac{g(2)-g(2-h)}{h}\\\\g'(2)=\lim_{h\to 0}\dfrac{0-(-h^2+2h)}{h}\\\\g'(2)=\lim_{h\to 0}\dfrac{h^2-2h}{h}\\\\g'(2)=\lim_{h\to 0}\dfrac{h(h-2)}{h}\\\\g'(2)=\lim_{h\to 0}(h-2)\\\\g'(2)=0-2\\\\g'(2)=-2

*******************************************
En général, la méthode classique pour déterminer g '(2) est celle-ci :

1) g(2) = -4 + 4 ===> g(2) = 0
    g(2+h) = -(2 + h)² + 2(2 + h)
               = -(4 + 4h + h²)  + 4 + 2h
               = -4 - 4h - h² + 4 + 2h
               = -h² - 2h

2) g'(2)=\lim_{h\to 0}\dfrac{g(2+h)-g(2)}{h}\\\\g'(2)=\lim_{h\to 0}\dfrac{(-h^2-2h)-0}{h}\\\\g'(2)=\lim_{h\to 0}\dfrac{-h^2-2h}{h}\\\\g'(2)=\lim_{h\to 0}\dfrac{h(-h-2)}{h}\\\\g'(2)=\lim_{h\to 0}(-h-2)\\\\g'(2)=0-2\\\\g'(2)=-2